Bentuk Dehumanisasi Dalam Novel “Surti Dan Tiga Sawunggaling” Karya Goenawan Mohammad - As. Shabiriyatun Nisa; Moh. Kholiqul Farisy; Sifatul Jannah; Mas’odi (Student Research Journal, 2025)
This research aims to describe the forms of dehumanization contained in the novel Surti and Tiga Sawunggaling by Goenawan Mohammad. The method used is descriptive qualitative with an objective approach. The research data is in the form of sentence quotations and dialogues in the novel that show the existence of human degradation. The data is obtained through literature study technique. The results show that there are several forms of dehumanization in the novel Surti and Tiga Sawunggaling. These forms of dehumanization include: 1. Dehumanization of slander, 2. Dehumanization of psychological impact, 3. Dehumanization of murder. Dehumanization in this novel is presented by Goenawan Mohammad to describe the social reality of Indonesian society during the revolutionary period.